EXPRESSION OF PREGNANCY ASSOCIATED GLYCOPROTEINS (PAGs) DURING DIFFERENT STAGES OF PREGNANCY - A MARKER FOR EARLY PREGNANCY DIAGNOSIS IN BUFFALOES - RANGASAMY, S; BALASUBRAMANIAN, S; VADIVOO, V S; BRINDHA, K; GOPIKRISHNAN, D; KULASEKAR, K (The Indian Journal of Animal Reproduction, 2023)
The pregnancy associated glycoproteins (PAGs) are a complex group of proteins secreted from themono- and bi-nucleate cells of the trophoblastic epithelium that have been used as early markers of pregnancy in bovines with varying accuracies. This experiment was designed to study the expression of PAG genes at different stages of pregnancy in buffalo. The PAG-1 and PAG-2 genes were identified as early markers of pregnancy at the feta-maternal interface in the pregnant uteri of buffaloes obtained from local abattoir and were found to be expressed from one to four month of pregnancy. In conclusion, PAGs could be used as one of the accurate markers of early pregnancy diagnosis in buffaloes.
Keywords: Glycoproteins; Pregnancy diagnosis; Buffaloes